Pemikiran Islam Wasathiyah Prof. Habib Abdullah Bin Muhammad Baharun - Ahmad Hanif Fahruddin; Tohirin (Akademika, 2025)
The attitude of moderation of Prof. Dr. Habib Abdullah Baharun is contained in his book entitled "Ushul al-Wasathiyah", namely: 1) Wahdah al-Ummah (Unity of the Ummah), 2) Al-Ghuluw wa al-Takfir (Exaggeration and Disbelief), 3) The Principle of Moderation in Islam which includes: a) Respecting the sentence of monotheism, b) Abandoning things that are not beneficial, c) Giving advice and reminding others. The conditions that must be met by people who want to convey advice and reminders to others, include: 1) Having good knowledge and understanding, 2) Being earnest, not wasting time, and avoiding repeating sentences that make the listener bored Islamic Thought, Wasathiyah, Abdullah Bin Muhammad Baharunwith the advice conveyed, 3) Focused, 4) Not too burdensome in giving advice, 5) Using beautiful and easy-to-understand sentences, and 6) Not intending to seek the world